2019
DOI: 10.1212/wnl.0000000000007475
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of seizure treatment in anti-LGI1, anti-NMDAR, and anti-GABA B R encephalitis

Abstract: ObjectiveThis nationwide cohort study evaluates seizure responses to immunotherapy and antiepileptic drugs (AEDs) in patients with anti-leucine-rich glioma-inactivated 1 (LGI1), anti-NMDA receptor (NMDAR), and anti-gamma-aminobutyric-acid B receptor (GABABR) encephalitis.MethodsAnti-LGI1, anti-NMDAR, and anti-GABABR encephalitis patients with new-onset seizures were included. Medical information about disease course, AEDs and immunotherapies used, effects, and side effects were collected. Outcome measures were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

24
286
4
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 212 publications
(318 citation statements)
references
References 28 publications
24
286
4
4
Order By: Relevance
“…The rationale for this choice is that: (a) a minority of patients, especially seronegative ones, could become seizure‐free using AEDs alone, and (b) patients can benefit from AEDs, even if immunotherapy fails . Of note, sodium‐channel blockers seem to be the most effective in achieving seizure freedom . On the other hand, it has been reported that levetiracetam might be less effective than carbamazepine in LGI1‐Ab encephalitis and its use limited by the risk of inducing and/or aggravating serious behavioral disorders …”
Section: Treatmentmentioning
confidence: 99%
See 4 more Smart Citations
“…The rationale for this choice is that: (a) a minority of patients, especially seronegative ones, could become seizure‐free using AEDs alone, and (b) patients can benefit from AEDs, even if immunotherapy fails . Of note, sodium‐channel blockers seem to be the most effective in achieving seizure freedom . On the other hand, it has been reported that levetiracetam might be less effective than carbamazepine in LGI1‐Ab encephalitis and its use limited by the risk of inducing and/or aggravating serious behavioral disorders …”
Section: Treatmentmentioning
confidence: 99%
“…Of note, sodium‐channel blockers seem to be the most effective in achieving seizure freedom . On the other hand, it has been reported that levetiracetam might be less effective than carbamazepine in LGI1‐Ab encephalitis and its use limited by the risk of inducing and/or aggravating serious behavioral disorders …”
Section: Treatmentmentioning
confidence: 99%
See 3 more Smart Citations